Keeping the faith [videorecording (DVD)] - Norton, Edward; Norton, Edward; Stiller, Ben, 1965-; Elfman, Jenna, 1971-; Wallach, Eli, 1915-2014; Bancroft, Anne, 1931-2005 (Touchstone Home Video ; Distributed by Buena Vista Home Entertainment, 2000)
Two men, long-time best friends, reunite with the tomboy who was the best friend of both; but all of them have changed-- greatly.